Policy Development for Environmental Sustainability of Agus-1 Hydroelectric Powerplant in Marawi City, Philippines - Motalib, Jalaloden M.; Sanchez, Kristine D. (Journal of Sustainability and Environmental Management, 2023)
Agus-1 Hydroelectric Powerplant is located within the mouth of Lake Lanao. This set-up is the most affecting factor which deteriorates the environmental health of the lake. In this reason, this study was conducted to assess the environmental sustainability of the lake and to generate policy development which is appropriate for implementation. The researcher collected data through water sample testing supported by survey instrument and focus group discussion. There were 200 respondents of the survey and it was found out that there is a consistent trend of those who rated no impact to low impact to all the sustainability indicators dictated. The results proved that the mandated agencies were ineffective and that the programs for re-vegetation, conducting fertilizing, seeding and plant tree seedling around the hydropower were not sufficient to keep the preservation of forest around the plant. Also, the water quality test results revealed that there was a presence of fecal coliforms, indicators of contamination of water in Lake Lanao. Thus, after data were extracted, the policy development was designed in focus of Environmental Excellency and Watershed Management.